2013
DOI: 10.1093/hmg/ddt597
|View full text |Cite
|
Sign up to set email alerts
|

Sun exposure causes somatic second-hit mutations and angiofibroma development in tuberous sclerosis complex

Abstract: Tuberous sclerosis complex (TSC) is characterized by the formation of tumors in multiple organs and is caused by germline mutation in one of two tumor suppressor genes, TSC1 and TSC2. As for other tumor suppressor gene syndromes, the mechanism of somatic second-hit events in TSC tumors is unknown. We grew fibroblast-like cells from 29 TSC skin tumors from 22 TSC subjects and identified germline and second-hit mutations in TSC1/TSC2 using next-generation sequencing. Eighteen of 22 (82%) subjects had a mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 20 publications
9
97
1
8
Order By: Relevance
“…Skin biopsies of hypomelanotic macules and nearby normal skin were obtained for cell culture. Fibroblasts were isolated as described previously (21). The melanocytes were isolated as described previously (90).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin biopsies of hypomelanotic macules and nearby normal skin were obtained for cell culture. Fibroblasts were isolated as described previously (21). The melanocytes were isolated as described previously (90).…”
Section: Methodsmentioning
confidence: 99%
“…We have recently shown that facial angiofibroma and other TSC cutaneous tumors are due to 2-hit mutational inactivation of both alleles of either TSC1 or TSC2 and that lesions on the face often sustain UV-induced CC>TT mutations in the second allele (21). Hypopigmented macules typically appear similar to an ash leaf in configuration, with relative hypopigmentation in comparison with surrounding skin, and are most commonly seen on the limbs and trunk (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Outro estudo recente, utilizando técnicas similares para sequenciamento de todos os éxons e a grande maioria intrônica de ambos os genes, não identificou mutações em 18% dos pacientes (Tyburczy et al, 2013 Knudson, 1971). …”
Section: A Aspectos Genéticos Do Tscunclassified
“…Perda de heterozigose foi demonstrada mais frequentemente para hamartomas do que hamártias de TSC (Au et al, 2004;Crino et al, 2010;Campos et al, 2013). Outros estudos relatam mutações de ponto como a mutação somática em hamartomas de pele desses pacientes (Tyburczy et al, 2013), o que não seria observado por métodos indiretos como perda de heterozigose. A limitação de demonstração da mutação somática em hamártia cerebral de pacientes com TSC, seja por método direto ou indireto, sugere haploinsuficiência da mutação germinativa (Niida et al, 2001;Wei et al, 2010).…”
Section: A Aspectos Genéticos Do Tscunclassified
See 1 more Smart Citation